Bus 174 - images of social humiliation (Psicologia USP, 2009)
This article presents a discussion about social psychology in the cinema through a specific concept: the social humiliation as a political problem. For this was taken as an object of analysis the film Bus 174, documentary directed by José Padilha in 2002. The comments produced here aim to understand the narrative strategies used by the director, which include aesthetic aspects and the participation of the public, that turn their work into an object of study of the social humiliation that occurs within the public sphere, where the action defines social relations among individuals.